Trends and sociodemographic factors of e‐cigarette use among adult daily smokers in South Korea. (26th December 2019) - Lee, Yen‐Han; Chiang, Timothy; Kwon, Elizabeth; Baik, Sohye; Chang, Yen‐Chang
Summary: Objective: Previous studies have identified the sociodemographic factors associated with e‐cigarette use among adolescents in South Korea. However, literature regarding e‐cigarette use among adult smokers remains limited in South Korea. Methods: Applying four waves (2013‐2016) of The Korea National Health and Nutrition Examination Survey (n = 3227), sociodemographic factors were included in the multivariable logistic regression model to study their relationships with e‐cigarette use among adult daily smokers. Results: E‐cigarette use increased from approximately 21.2% to 34.6% from 2013 to 2016, respectively. Females had lower odds of e‐cigarette use (adjusted odds ratio [AOR] = 0.76; 95% CI, 0.58‐0.99, P < .05) compared with males. Older age was negatively associated with e‐cigarette use experience (all P s < .01). Daily smokers with high school education or above all had higher odds of using e‐cigarettes compared those with elementary school education (all P s < .05). Conclusion: As this study examined the trends of e‐cigarette use and factors associated with e‐cigarette use among adult daily smokers in South Korea, further research is needed to investigate the long‐term effect of e‐cigarette use on smoking cessation in South Korea as well as other Asian countries.